COVID-19 Sport Transformation: New Challenges and New Opportunities - Glebova Ekaterina; Zare Fateme; Desbordes Michel; Géczi Gábor (Sciendo, 2022)
The new pandemic lifestyle advocates new rules for sport at all levels, from amateur to elite. Consequently, it has transformed the ways in which sports are performed and consumed, provoking demand for new technologies and/or the development of existing ones. This paper aims to identify, describe, and visualize the process of sport transformation as radical internal and external industry changes brought about by the COVID-19 pandemic. It is intended to qualitatively explain the current 'metamorphoses' in the field and subsequently answer the question of how the COVID-19 pandemic drastically changed all aspects of sports and physical culture. The literature and empirical dataset (qualitative open-ended written interviews, N = 147) were analysed in the spirit of grounded theory, referring to the holistic approach. The results demonstrated that the COVID-19 pandemic has had an unprecedented effect on sports by touching on all aspects, levels, and stakeholders. The paper also outlines challenges and opportunities for the industry in these extraordinary times. The key dimensions of transformation are identified and explained. The findings of this research have significant implications for the understanding of how COVID-19 gave rise to the transformation of sports in different aspects. This study adds to the growing body of research on the positive and negative impacts of COVID-19 on sports, new technologies demand, and the transformation of sports.